CONGENITAL HEART DEFECTS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
Congenital heart defects (CHDs) represent one of the most common congenital anomalies worldwide, affecting approximately 1% of live births. They range from simple defects, such as atrial septal defects, to complex malformations like tetralogy of Fallot and hypoplastic left heart syndrome. This paper provides a comprehensive overview of CHDs, focusing on classification, pathophysiology, diagnostic tools, and treatment strategies. Advanced imaging techniques, such as fetal echocardiography and cardiac MRI, play an integral role in early detection and management